Do Both Petty and Serious Female Offenders Have Shorter Incarcerations than Their Male Counterparts? Testing the Universality of Chivalrous Treatment - Liu, Lin (Women & criminal justice, 2023)
While numerous studies have unpacked gender-based disparities in judges’ sentencing decisions, few studies have examined the gender gap in correction settings. This study examines inmates’ gender gap in actual incarceration length with the effects of criminal propensities adjusted. Based on a sample including both petty and serious offenders, we use survival analysis to examine whether female inmates had shorter incarcerations to similarly situated males. We use Wilcoxon signed-rank tests to examine whether males and females who had indistinguishable lengths of incarcerations also demonstrated comparable levels of criminal propensities. Findings illustrate that the lenient treatment for females is conditional rather than universal. Females had shorter incarceration lengths only when they committed less severe crimes. Additionally, among offenders who committed less severe crimes, females demonstrated significantly lower levels of criminal propensity than males. However, among serious offenders, neither a gender gap in incarceration length nor gender disparity in criminal propensities was found.